Little Ice Age Glacial Geomorphology and Sedimentology of Portage Glacier, South-Central Alaska. - Santos, João; Cordova, Carlos (Finisterra, 2009)
The study of glacial landforms and deposits is important, as it is difficult to observe processes under modern glaciers and ice-sheets. Thus landscapes and sediments that are the product of present glaciation can give insight into processes that occurred during Pleistocene times. This study investigates the genesis of little ice age glacial landforms present in Portage Glacier, South-Central Alaska. The present day moraine morphology and sedimentology in Portage Glacier valley reveals the presence of two types of till and moraines. The clast-rich sandy diamicton present on the 1852 moraine is interpreted to be a basal till indicating this feature is a push moraine representing an advance or a standstill position of Portage Glacier in 1852. The moderately sorted gray sandy boulder gravel present on the 1900 and 1922 moraines is interpreted to be an ice-marginal deposit (ablation till) with a mixture of supraglacial and glaciofluvial sediments deposited by slumping and stream sorting processes. All of these features are interpreted to be ablation moraines representing glacier retreat and moraine building in 1900 and1922